Effect of sowing methods and weeding regimes on the yield of Sesame (Sesamum indicum L.) - Khanam, Afroza; Salam, Md Abdus; Uddin, Md Romij; Rabbani, Md Golam; Hoshain, Shohrab (Research in Agriculture Livestock and Fisheries, 2022)
The experiment was conducted at the Agronomy Field Laboratory, Bangladesh Agricultural University to observe the effect of sowing methods and weeding regimes on the yield of sesame. The experiment comprised of two factors. Two methods of sowing i.e., broadcasting and line sowing (S2), and six weeding regimes- control (T0), weed free (T1), one hand weeding at 15 DAS (T2), two hand weedings at 15 and 30 DAS (T3), three hand weedings at 15, 30 and 45 DAS (T4) and application of Panida (Pendimethalin) herbicide (T5) at 3 DAS. The experiment was laid out in a randomized complete block design (RCBD) with three replications. Almost all the yield characters of sesame were affected significantly due to sowing methods, weeding regime and their interaction. Result showed that the l ine sowing showed better performance regarding plant height (100.40 cm), number of branches (4.983) plant–1, number of capsules plant–1 (47.82), number of seeds capsule–1 (69.66), 1000–seed weight (2.96 g), seed yield (956.90 kg ha–1), stover yield (2167.0 kg ha–1), biological yield (3123.00 kg ha–1) and harvest index (31.45%) than that of broadcasting method. Also weed free treatment had the highest plant height (101.90 cm), highest number of branches (5.00) plant-1, highest capsule (47.08) plant–1, heaviest 1000–seed weight (3.28 g), highest number of seeds capsule–1 (76.22), highest seed yield (974.30 kg ha–1), stover yield (2947.0 kg ha–1) and biological yield (3922.0 kg ha–1) as compared to other treatments while unweeded plot had least significant effect among the whole yield and yield attributes of sesame. In case of interactions, both weed free treatment and herbicidal effect with line sowing methods produced the highest plant height, number of branches and capsules plant–1, seeds capsule–1, seed yield, stover yield and biological yield (109.80 cm, 5.967, 56.57, 81.53, 1054.0 kg ha–1, 3139.0 kg ha–1 and 4193.0 kg ha–1, respectively) as compared to other interaction combinations. The results of the study reveal that the weed free treatment along with line sowing would be the proper technique for higher production of sesame. But line sowing along with application of Panida herbicide would be the best combination for obtaining higher yield of sesame since it is not feasible for the farmers to keep their field weed free throughout all the growing periods. Res. Agric., Livest. Fish.8(3): 291-299, December 2021